Strategi Brain-Based Learning Untuk Penguatan Kejujuran Dan Pencegahan Penyalahgunaan Data Akuntansi - Adrian Hartanto Darma Sanputra; Eka Ananta Sidharta; Tatas Ridho Nugraha; Elsa Isnaini Putri; Azzahra Azzahra (Universitas Negeri Gorontalo, 2025)
Early exposure to unethical accounting practices risks normalizing data manipulation, so instilling honesty from an early age is important. This community service program employs Brain-Based Learning (BBL) to strengthen students' integrity through the 4P model (Preparation, Implementation, Closure, Reporting) by incorporating neuroscience-based activities such as brain gym, gamification, reflective discussions, and parental involvement. The results are highly significant: students' understanding of integrity increased from 32% to 89%, 76% of students reported a shift in their perspective on ethical dilemmas, and parents shifted their focus from academic performance to character development, forming a support community named “Parents Concerned About Integrity.” The BBL approach has proven to create optimal cognitive conditions for internalizing the value of honesty and reducing the risk of accounting data misuse. Program outputs include modular learning packages, teacher training syllabi, parent support group tools, and the establishment of integrity champions to expand reach and sustainability. This combination of policies and products is expected to institutionalize integrity education and reduce the risk of accounting data misuse.